2005
DOI: 10.1126/science.1111410
|View full text |Cite
|
Sign up to set email alerts
|

Direct Control of Germline Stem Cell Division and Cyst Growth by Neural Insulin in Drosophila

Abstract: Stem cells reside in specialized niches that provide signals required for their maintenance and division. Tissue-extrinsic signals can also modify stem cell activity, although this is poorly understood. Here, we report that neural-derived Drosophila insulin-like peptides (DILPs) directly regulate germline stem cell division rate, demonstrating that signals mediating the ovarian response to nutritional input can modify stem cell activity in a niche-independent manner. We also reveal a crucial direct role of DIL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
311
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(344 citation statements)
references
References 20 publications
25
311
0
1
Order By: Relevance
“…In mice, an unknown factor or factors from the young systemic environment can rejuvenate aged muscles and hepatic stem/precursor cells through upregulating the Notch signaling pathway [56]. Two recent exciting studies in the Drosophila ovary have identified insulin as a systemic factor for controlling GSC proliferation [57,58]. The GSCs defective in insulin signaling divide much slower than wild-type ones.…”
Section: Genes and Pathways That Control Gsc Self-renewal Proliferatmentioning
confidence: 99%
“…In mice, an unknown factor or factors from the young systemic environment can rejuvenate aged muscles and hepatic stem/precursor cells through upregulating the Notch signaling pathway [56]. Two recent exciting studies in the Drosophila ovary have identified insulin as a systemic factor for controlling GSC proliferation [57,58]. The GSCs defective in insulin signaling divide much slower than wild-type ones.…”
Section: Genes and Pathways That Control Gsc Self-renewal Proliferatmentioning
confidence: 99%
“…Another signal secreted from the niche, Hedgehog (Hh), also contributes to GSC self-renewal (King et al ., 2001). In addition to the regulation by the local environment, neuronal insulin-like peptide secreted from the brain regulates GSC division through activation of the insulin receptor signaling activity in GSCs (LaFever & Drummond-Barbosa, 2005). Nutrition mediated through the insulin pathway also affects GSC activity (Drummond-Barbosa & Spradling, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly, brain-expressed Dilps have been shown to act directly upon GSC, controlling the production of new egg chambers (LaFever and Drummond-Barbosa, 2005). Ablation of Dilp-secreting neurons, or, genetic disruption of the Drosophila-insulin receptor within the germline (as shown by mosaic analysis) both result in severely compromised GSC production of new egg chambers (LaFever and Drummond-Barbosa, 2005).…”
Section: Fhv Infection Correlates With Altered Expression Of Drosophimentioning
confidence: 99%
“…Ablation of Dilp-secreting neurons, or, genetic disruption of the Drosophila-insulin receptor within the germline (as shown by mosaic analysis) both result in severely compromised GSC production of new egg chambers (LaFever and Drummond-Barbosa, 2005). When flies are placed under nutritional restriction, dilp3 and dilp5 levels decrease while dilp2 expression remains unchanged (Ikeya et al, 2002).…”
Section: Fhv Infection Correlates With Altered Expression Of Drosophimentioning
confidence: 99%